Marine Conservation Outcomes are More Likely when Fishers Participate as Citizen Scientists: Case Studies from the Mexican Mesoamerican Reef. (5th June 2018) - Fulton, Stuart; Caamal-Madrigal, Jacobo; Aguilar-Perera, Alfonso; Bourillón, Luis; Heyman, William D.
Small-scale fishers on Caribbean coral reefs have exploited fish spawning aggregations (FSAs) for generations, but intense fishing has led to the loss of traditional aggregation sites. In many areas, the traditional ecological knowledge (TEK) of fishers has contributed greatly to the characterization of spawning aggregations and implementation of local conservation initiatives. TEK has identified more than 40 potential FSA sites along the coast of the Mexican Mesoamerican Reef. These sites have been characterised and scientifically validated, in some cases with traditional western science and in others, with a participatory citizen-science approach. The objective of this work is to compare the science and conservation outcomes at these FSA sites. We report that those FSA sites where scientific surveys were conducted without community participation remain unprotected. By contrast, the FSAs where local fishers were engaged in characterization and subsequent monitoring are now protected at the behest of the fishers themselves. Conservation initiatives to protect FSAs can be more effective through a combination of TEK, western science, and participatory citizen science involving local fishers.